The Interaction between Nonexpected Utility and Asymmetric Market Fundamentals - HUNG, MAO‐WEI (Journal of Finance, 1994)
ABSTRACT This paper studies a nonexpected utility, general equilibrium asset pricing model in which market fundamentals follow a bivariate Markov switching process. The results show that nonexpected utility is capable of exactly matching the means of the risk‐free rate and the risk premium. Asymmetric market fundamentals are capable of generating a negative sample correlation between the risk‐free rate and the risk premium. Moreover, an equilibrium asset pricing model endowed with asymmetric market fundamentals is consistent with all five first and second moments of the risk‐free rate and the risk premium in the U.S. data.